The Challenges Facing Effective Teaching, Learning and Assessment in Community-Based Secondary Schools in Tabora Region. - Assey, Ernest S; Babyegeya, Emmanuel (American Journal of Education and Practice, 2022)
Purpose: This study focused on the challenges facing effective teaching, learning and assessment in community-based secondary schools in the Tabora region. Methodology: This study employed a mixed method approach in line with a sequential explanatory research design. The study employed simple random sampling procedures to enlisted 219 people from various educational backgrounds. Questionnaires and semi-structured interviews were used to gather information. Results: The study findings revealed that, poor teaching and learning environments, a problem with the medium of instructions, poor parental engagement in children's education, teacher shortages, poor managerial skills among school leaders and lack of in-service training among teachers are the main factors that hinder effective teaching, learning and assessment in community-based secondary schools in Tabora region in Tanzania. Unique contribution to practice, theory and strategy: This study contributes to a better understanding of the challenges to effective teaching, learning and assessment in Tanzania's Tabora region's community-based secondary schools. The findings are comparable with "Curriculum theory," which emphasised that an effective curriculum implementation cannot take place in a setting where there is a lack of a supportive environment, where significant school stakeholders do not collaborate in planning for teaching and assessment, where there is a fairly poor teaching and learning environment, where there are not enough human resources, and where the language of instruction is inappropriate. Recommendation: The local authority that oversees schools should hire more teachers, upgrade the facilities for teaching and learning, fully involve parents in decision-making, improve in-service teacher training, and require school administrators to regularly attend training on pedagogical leadership in order to implement effective teaching, learning and assessment in schools.